Observation of filamentous nanostructures in organic-inorganic composite thin films deposited by co-evaporation - Donhauser, Daniela; Pfannmöller, Martin; Dieterle, Levin; Schultheiß, Katrin; Schröder, Rasmus R.; Kowalsky, Wolfgang; Kröger, Michael (Advanced functional materials, 2013)
Nanostructures are important for a wide area of applications, but are very often difficult to fabricate. A novel and basic approach for controlled nanofilament growth in an organic/inorganic composite material is demonstrated. Thin films of MoO3-doped 4′-bis(N-carbazolyl)-1,1′-biphenyl are grown via vacuum sublimation and analyzed using advanced electron microscopy and spectroscopy techniques. Using electron spectroscopic imaging in the core-loss and low-loss regime, MoO3 agglomerations are identified for different doping concentrations. A 3D reconstruction of the thin film yielded by electron tomography reveals a filamentous structure of MoO3 within the organic matrix. These filaments are preferentially oriented along the growth direction and are only a few nanometers in diameter. Furthermore, control of the filament growth is possible by changing the substrate temperature because for composites grown on substrates cooled to 120 K MoO3 agglomeration cannot be detected.